2018
DOI: 10.1186/s12936-018-2257-x
|View full text |Cite
|
Sign up to set email alerts
|

Elevated IL-17 levels in semi-immune anaemic mice infected with Plasmodium berghei ANKA

Abstract: BackgroundAlterations in inflammatory cytokines and genetic background of the host contribute to the outcome of malaria infection. Despite the promising protective role of IL-17 in infections, little attention is given to further understand its importance in the pathogenesis of severe malaria anaemia in chronic/endemic situations. The objective of this study, therefore, was to evaluate IL-17 levels in anaemic condition and its association with host genetic factors.MethodsTwo mice strains (Balb/c and CBA) were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
11
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 34 publications
1
11
0
Order By: Relevance
“…It has been suggested that both cytokines provide protection against infection [15]. Furthermore, elevated levels of IL-17 with high levels of IL-4, IL-12 and IFNγ were associated with hemoglobin loss in malaria recovered semi-immune mice [41]. Fitri et al [42] reported that an imbalance between IL-17 and IL-10 caused low foetal weight in P. berghei infection in mice.…”
Section: Discussionmentioning
confidence: 99%
“…It has been suggested that both cytokines provide protection against infection [15]. Furthermore, elevated levels of IL-17 with high levels of IL-4, IL-12 and IFNγ were associated with hemoglobin loss in malaria recovered semi-immune mice [41]. Fitri et al [42] reported that an imbalance between IL-17 and IL-10 caused low foetal weight in P. berghei infection in mice.…”
Section: Discussionmentioning
confidence: 99%
“…It has been suggested that both cytokines provide protection against infection [15]. Furthermore, elevated levels of IL-17 with high levels of IL-4, IL-12 and IFNγ were associated with haemoglobin loss in malaria recovered semi-immune mice [41]. Fitri et al [42] reported that an imbalance between IL-17 and IL-10 caused low fetal weight in Plasmodium berghei infection in mice.…”
Section: Discussionmentioning
confidence: 99%
“…Inadequate B cell memory recall and Plasmodium immunomodulation of host responses are likely involved (reviewed in Frosch and John 2012 ). When studying Plasmodium , well-established malaria mouse infection models are often utilised to investigate pathogenesis, immunomodulation, anaemia, liver-stage infections and blood-stage infections (Helegbe et al 2018 ; Lau et al 2014 ; Ryg-Cornejo et al 2016b ). To do this, administration of low doses (10 mg/kg each) of chloroquine (CQ) and pyrimethamine (Pyr) are crucial to prevent the progression of disease and effectively clear the infection in these mice (Schofield et al 2017 ).…”
Section: Introductionmentioning
confidence: 99%